In vivo assessment of extracellular pH of joint tissues using acidoCEST-UTE MRI - High, Rachel A.; Ji, Yang; Ma, Ya-Jun; Tang, Qingbo; Murphy, Mark E.; Du, Jiang; Chang, Eric Y. (Quantitative Imaging in Medicine and Surgery, 2019)
Background: Degradation of cartilage and meniscus may be mediated by changes in extracellular pH. The purpose of this study was to optimize saturation powers used with the acidoCEST magnetic resonance imaging (MRI) technique with a 3D ultrashort echo time readout (acidoCEST-UTE) and to demonstrate feasibility of the method for measuring pH in cartilage and meniscus in vivo. Methods: Magnetization transfer ratio asymmetry and ratio of radiofrequency (RF) power mismatch at different powers were evaluated in cartilage and meniscus tissue phantoms for iopamidol and iohexol. Using optimized RF powers, the acidoCEST-UTE MRI sequence was used to assess pH of joint fluid and tissues in four patients after direct intra-articular administration of iodinated contrast. Results: In the phantoms, the ratio of powers 0.54/1.10 µT showed the strongest correlation with pH. In vivo acidoCEST-UTE pH measurements of intra-articular fluid were similar to electrode measurements of the contrast agent (7.22 vs. 7.1 for iopamidol, respectively; 7.65 vs. 7.5 for iohexol, respectively). As measured with the acidoCEST-UTE technique, overall mean cartilage pH was significantly lower than overall mean meniscus pH (6.60 vs. 6.72, respectively; P=0.043). Conclusions: AcidoCEST-UTE MRI after direct intra-articular administration of either iopamidol or iohexol can be used to measure cartilage and meniscus pH in vivo.